LITERATUR REVIEW : PERAN APOTEKER DALAM PENCEGAHAN MEDICATION ERROR PADA PASIEN PEDIATRIK - Anggraeni, Rieka Nurul Dwi (FACULTY OF PHARMACY, INSTITUT ILMU KESEHATAN BHAKTI WIYATA, 2025)
Background: Medication errors (MEs) in pediatric patients are a serious patient safety concern. MEs in children often occur due to insufficient understanding of pediatric dosing and non-compliance with standard operating procedures (SOPs) by healthcare professionals. Objective: This article aims to review the role of pharmacists in preventing MEs in pediatric patients through an analysis of recent literature. Methods: The article was prepared as a literature review using sources from online databases (ScienceDirect, PubMed, Google Scholar) published between 2020 and 2025. Inclusion criteria included full-text availability, relevance to the topic, and focus on the pediatric context. Results: Several studies show that pharmacist interventions, such as prescription review, education, audit, medication reconciliation, and participation in ward rounds, can reduce the incidence of MEs by 64–73%. Studies in Indonesia revealed that 92% of pediatric prescriptions did not include body weight and only 16% contained complete information, indicating a high potential for dosing errors. Pharmacist-led education for healthcare providers and parents/caregivers plays an important role in improving understanding and preventing medication administration errors at home. Conclusion: Pharmacists play a crucial role in preventing pediatric MEs through clinical and educational interventions. Active pharmacist involvement in multidisciplinary teams is strongly recommended to improve pediatric patient safety.